PENGARUH KUALITAS PRODUK, HARGA, PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN TOKO MAS SEMAR DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MODERASI - Erni Widajanti, Dwi Abadi, Alwi Suddin & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2018)
The purpose of this research are to analyze the significant impact ofproduct quality, price, promotion, and customer satisfaction on purchasedecision and to determine how customer satisfaction can moderate theproduct quality, price, and promotion on purchase decision. The aim of thisresearch is to give Toko Emas Semar Pasar Kalioso recommendation toincrease their revenue and to become a reference for other researchers. Thepopulation of this research are 100 customer of Toko Emas Semar PasarKalioso. This research using survey questionnaire method. The technique ofdata analysis of this research is multiple linear regression analysis, T-test, Ftest,coefficient determination, and absolute deviation. The result of thisresearch shows that the product quality does not affect significantly onpurchase decision of the costumers, the price affects significantly onpurchase decision of the costumers, promotion affects significantly onpurchase decision of the costumers, customer satisfaction affectssignificantly on purchase decision of the costumers, customer satisfactiondoes not moderate the effect of product quality on purchase decision of thecustomers, customer satisfaction does not moderate the effect of productquality on purchase decision of the customer, and customer satisfactionmoderates the effect of promotion on purchase decision of customer in TokoEmas Semar Pasar Kalioso.Keywords: Product Quality, Price, Promotion, Satisfaction, PurchaseÂ